EVALUASI DOKUMEN PERENCANAAN GEDUNG KANTOR BALAI PELAKSANA PEMILIHAN JASA KONSTRUSI (BP2JK) WILAYAH SUMATERA SELATAN - Azzahra Dwi Lintang Sakina; Firdaus Firdaus (Rang Teknik Journal, 2026)
The evaluation of office building planning documents is a crucial step in ensuring the quality of construction project implementation. This study aims to evaluate the completeness and compliance of the planning documents for the Office Building of the Construction Services Procurement Unit (BP2JK) of South Sumatra Region, referring to the applicable technical standards and regulations. The research employs a qualitative descriptive method through document study and direct observation of planning components. The evaluation results indicate that most documents meet administrative and technical requirements, although some elements require improvements to ensure technical clarity and smooth project implementation. These findings highlight the importance of systematic planning document preparation as the foundation for the success of public construction projects. The study also recommends enhancing quality control mechanisms in the planning process and utilizing information technology to support document accuracy and transparency.  Keywords: document evaluation, building planning, public construction, BP2JK, quality control